2016
DOI: 10.1016/j.yhbeh.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone attenuates impulsive action in a Go/No-Go task for sucrose pellets in female and male rats

Abstract: Impulsivity, or a tendency to act without anticipation of future consequences, is associated with drug abuse. Impulsivity is typically separated into two main measures, impulsive action and impulsive choice. Given the association of impulsivity and drug abuse, treatments that reduce impulsivity have been proposed as an effective method for countering drug addiction. Progesterone has emerged as a promising treatment, as it is associated with decreased addiction-related behaviors and impulsive action. The goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…However, a few studies have shown contradictory results (Fields et al, 2009) or no sex differences (Reynolds et al 2004; Townshend and Duka 2005; Fernie et al 2010). Previous results in our laboratory are consistent with the preclinical literature, as female rats made more premature errors in a Go/No-go task for cocaine (Anker et al 2008), and in a few other studies there were no sex differences in impulsive action with mice (Papaleo et al 2012) and rats (Anker et al 2008; Swalve et al, 2016a). In general, data are mixed on sex differences in impulsive action (see review by Fattore and Melis 2016), and little is known about the interaction between sex and impulsive action for cocaine use and its treatment.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, a few studies have shown contradictory results (Fields et al, 2009) or no sex differences (Reynolds et al 2004; Townshend and Duka 2005; Fernie et al 2010). Previous results in our laboratory are consistent with the preclinical literature, as female rats made more premature errors in a Go/No-go task for cocaine (Anker et al 2008), and in a few other studies there were no sex differences in impulsive action with mice (Papaleo et al 2012) and rats (Anker et al 2008; Swalve et al, 2016a). In general, data are mixed on sex differences in impulsive action (see review by Fattore and Melis 2016), and little is known about the interaction between sex and impulsive action for cocaine use and its treatment.…”
Section: Introductionsupporting
confidence: 90%
“…The rationale for studying the effect of PRO on impulsive action is based on our previous finding that PRO reduced impulsive choice for cocaine in female but not male rats (Smethells et al 2016). Also, in another recent study PRO reduced impulsive action for sucrose pellets in both female and male rats (Swalve et al 2016a). Thus there may be differences in the effect of PRO on drug- vs. natural-rewards such as sucrose (Swalve et al 2016a).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Further, progesterone has been shown to improve response inhibition in both preclinical and clinical studies. In a Go/No-Go food task, rats treated with progesterone showed decreased impulsivity (Swalve et al, 2016). In clinical laboratory studies, our group has demonstrated that progesterone, both endogenous, in abstinent female smokers in luteal phase, and exogenous, 200 mg/day in current female smokers, improves cognitive performance on a Stroop task (DeVito et al, 2014; Sofuoglu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%